(untitled) (European Journal of Pure and Applied Mathematics, 2025)
Our aim in this work is to derive conditions and criteria for the oscillation of some differential equations of p-Laplace type with a delayed term. Therefore, we develop these criteria that confirm to us that the equations studied are oscillatory by applying comparison with lower-order equations and Riccati techniques . Finally, we can elucidate the meaning of the new inequalities by applying our findings to a few particular cases of the studied equation. Our findings build on earlier findings that looked at equations with a delay term and operators of the p-Laplace type. To demonstrate the importance of the acquired results, we provide an example.